2018
DOI: 10.1002/dvdy.24638
|View full text |Cite
|
Sign up to set email alerts
|

Integral bHLH factor regulation of cell cycle exit and RGC differentiation

Abstract: Our data support the hypothesis that Neurog2 acts at the top of a retinal bHLH transcription factor hierarchy. The combined expression levels of these downstream factors are sufficiently induced by ectopic Ascl1 to restore RGC genesis, highlighting the robustness of this gene network during retinal ganglion cell neurogenesis. Developmental Dynamics 247:965-975, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Alternatively, Neurog2 is known to control cell cycle exit in the brain, via its stimulation of the cyclin-dependent kinase inhibitor p27/Kip1(Cdkn1b) (Farah et al, 2000; Lacomme et al, 2012; Nguyen et al, 2006). In E12.5 Neurog2 germline mutants, we found a longer than normal cell cycle (Maurer et al, 2018), thereby pushing the window for retinal ganglion cell differentiation. Thus, a delay in any retinal neuron birthdate might bias the genesis of relatively later cell types.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alternatively, Neurog2 is known to control cell cycle exit in the brain, via its stimulation of the cyclin-dependent kinase inhibitor p27/Kip1(Cdkn1b) (Farah et al, 2000; Lacomme et al, 2012; Nguyen et al, 2006). In E12.5 Neurog2 germline mutants, we found a longer than normal cell cycle (Maurer et al, 2018), thereby pushing the window for retinal ganglion cell differentiation. Thus, a delay in any retinal neuron birthdate might bias the genesis of relatively later cell types.…”
Section: Discussionmentioning
confidence: 81%
“…In a separate study about the initial wave of retinal neurogenesis, we performed a transcriptomics analysis of purified GFP+ RPCs from E12.5 Neurog2 GFP/ + and Neurog2 GFP/GFP eyes (Maurer et al, 2018). Here Blimp1 mRNA levels were already significantly reduced in the absence of Neurog2 (n = 3 biologic replicates/genotype).…”
Section: Resultsmentioning
confidence: 99%
“…However, further investigation is required to identify and characterize Nhlh1(+) developing cone photoreceptors and determine whether they develop from the ECR65(+) population. Similarly, NeuroG2 has been found to be important for RGC genesis [18,30] and involved in HC fate choice [2]. This role may underlie its interaction with ECR9 ( Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, Atoh7 is one of the first pro-neuronal transcription factors and is essential for the production of the first neurons, RGC, in the zebrafish retina (Kay et al, 2001;Masai et al, 2000). Thus, it suggested that cells of this cluster were undergoing initiation of the neuronal differentiation program (Chiodini et al, 2013;Maurer et al, 2018). This cluster of cells constituted only a small fraction of 24-hpf RPCs (4.7%, Fig.…”
Section: Defining Cellular Heterogeneity Of Embryonic Rpcsmentioning
confidence: 99%